Homocysteine Aggravates Intestinal Epithelial Barrier Dysfunction in Rats with Experimental Uremia - Shanshan Liang; Sixiu Liu; Hua Liu; Xin He; Lingshuang Sun; Lei Chen; Meng Wei; Fanfan Gao; Hongli Jiang (Karger Publishers, 2018)
Background/Aims: Previous studies have shown that homocysteine (Hcy) is an important intestinal-derived uremic toxin. However, whether Hcy is involved in the epithelial barrier dysfunction observed in uremia remains unclear. This study aimed to investigate the effect of Hcy on intestinal permeability and intestinal barrier structure and function in adenine-induced uremic rats. Methods: Sprague-Dawley rats were divided into five groups: normal control (group NC), Hcy (group H), uremia (group U), uremia + Hcy (group UH), and uremia + Hcy + VSL#3 (group UHV). Experimental uremia was induced by intragastric adenine administration, and Hcy was injected subcutaneously. The animal models were assessed for renal function and pathological tissue staining. The pathological changes of intestinal tissue were observed by hematoxylin and eosin staining and electron microscopy. The serum and intestinal tissue levels of Hcy, interleukin (IL)-6, tumor necrosis factor (TNF)-α, superoxide dismutase (SOD), and malondialdehyde (MDA) as well as serum endotoxin and intestinal permeability were assessed. The levels of the tight junction proteins claudin-1, occludin, and zonula occludens-1 (ZO-1) were assessed by western blotting. Results: Blood analyses and renal pathology indicated that experimental uremia was induced successfully. Pathological damage to intestinal structure was most obvious in group UH. Serum and tissue Hcy, serum endotoxin, and intestinal permeability were significantly elevated in group UH. The protein levels of claudin-1, occludin, and ZO-1 were decreased to various degrees in group UH compared with groups NC, H, and U. The serum and tissue levels of IL-6, TNF-α, and MDA were significantly increased, while SOD activity was markedly decreased. Supplementation with the probiotic VSL#3 improved these parameters to various degrees and up-regulated the abundance of tight junction proteins, which indicated a role for Hcy in the increase of intestinal permeability and destruction of the epithelial barrier in uremia. Conclusion: Hcy aggravates the increase of intestinal permeability and destruction of the epithelial barrier by stimulating inflammatory and oxidative damage. Probiotic administration can ameliorate this damage by reducing the levels of Hcy-induced inflammation and oxidation.